A case of relapsing iritis with hypopyon: translation of the original account of Benediktos Adamantiades. (30th June 2016) - Matteson, Eric L
Benediktos Adamantiades presented an account of a 20-year-old male with oral and genital aphthosis, pyoderma and arthritis at a meeting of the Medical Association of Athens in November 1930. His case subsequently published in Greek, and then in French in 1931, and is recognized through the dual eponym 'Adamantiades–Behçet disease' by many current investigators. Adamantiades subsequently added other observations to the syndrome, and developed the first classification and diagnostic criteria for it. The translation of his work from French to English is offered to provide accessibility to a wider audience interested in the history of what is commonly called Behçet disease.